PENDIDIKAN ISLAM DALAM BERBAGAI SUDUT PANDANG - Rahman, Aulia; Aprison, Wedra (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
Islamic education is a symbol of the teachings of Islam itself which we must always advance and improve so that we can compete on the one hand, as well as meet the needs of society. Thus, graduates from Islamic educational institutions can contribute more to the state, nation, society and religion. For this reason, Islamic education must always be updated so that it continues to exist in the midst of the progress of the times. Islamic education really needs to be studied in all aspects of perspective in order to enrich the treasures of the concept of Islamic education itself. Therefore, this paper tries to examine Islamic education from the point of view of the history of Islamic education and the spirit of developing science as a reference in building a monumental Islamic education so that it can restore the glory of Islam.